Anterior Cingulate Implant for Alcohol Dependence: Case Report. Issue 6 (June 2016) - De Ridder, Dirk; Manning, Patrick; Glue, Paul; Cape, Gavin; Langguth, Berthold; Vanneste, Sven
Abstract : BACKGROUND AND IMPORTANCE: Alcohol dependence is related to dysfunctional brain processes, in which a genetic background and environmental factors shape brain mechanisms involved with alcohol consumption. Craving, a major component determining relapses in alcohol abuse, has been linked to abnormal brain activity. CLINICAL PRESENTATION: We report the results of a treatment-intractable, alcohol-addicted patient with associated agoraphobia and anxiety. Functional imaging studies consisting of functional magnetic resonance imaging and resting-state electroencephalogram were performed as a means to localize craving-related brain activation and for identification of a target for repetitive transcranial magnetic stimulation and implant insertion. Repetitive transcranial magnetic stimulation of the dorsal anterior cingulate cortex with a double-cone coil transiently suppressed his very severe alcohol craving for up to 6 weeks. For ongoing stimulation, 2 "back-to-back" paddle electrodes were implanted with functional magnetic resonance imaging neuronavigation guidance for bilateral dorsal anterior cingulate cortex stimulation. Using a recently developed novel stimulation design, burst stimulation, a quick improvement was obtained on craving, agoraphobia, and associated anxiety without the expected withdrawal symptoms. The patient has remained free of alcohol intake and relieved of agoraphobia and anxiety for over 18 months, associated with normalization of his alpha and beta activity on electroencephalogram in the stimulated area. He perceives a mental freedom by not being constantly focused on alcohol. CONCLUSION: This case report proposes a new pathophysiology-based target for the surgical treatment of alcohol dependence and suggests that larger studies are warranted to explore this potentially promising avenue for the treatment of intractable alcohol dependence with or without anxiety and agoraphobia. ABBREVIATIONS: ACC, anterior cingulate cortex BOLD, blood oxygen level dependent dACC, dorsal anterior cingulate cortex DBS, deep brain stimulation EEG, electroencephalogram fMRI, functional magnetic resonance imaging rTMS, repetitive transcranial magnetic stimulation SMA, supplementary motor area TMS, transcranial magnetic stimulation Abstract : Supplemental Digital Content is available in the text.